Neck - tongue syndrome: rare case report - Filho, Amauri Pereira da Silva; Reis, Taianara Sampaio; Romano, Danielle Cortellazzi Colonna; Nakamura, Gabriela Yumi; Freitas, Melissa Fernandes Vilela de; Batista, Sabrina Borges; Karpejany, Natália Rebeca Alves de Araújo (Headache Medicine, 2024)
INTRODUCTION: Neck-tongue syndrome (NTS) is a very rare clinical condition defined by the International Headache Society (IHS) as “painful lesions of the cranial nerves and other facial pain”. The headache disorder is often initiated by rapid axial rotation of the neck resulting in unilateral neck and/or occipital pain and transient ipsilateral tongue sensory disturbance. It is still very underrecognized, predominantly affecting children and adolescents. The prevalence is slightly higher in women. The pathophysiology mainly results from ligamentous laxity during growth, leading to transient subluxation of C1-C2 with sudden head movements. In the branch of the lingual nerve, where the anastomosis with the hypoglossal nerve is impacted against the bone, symptoms occur in the tongue. Diagnosis is based on clinical suspicion after a thorough history and physical examination, without a pathognomonic radiologic finding. It is typically treated conservatively with medications, local injections, immobilization with cervical collars, or physical therapy; rarely is surgical intervention pursued.OBJECTIVE: Describing and recognizing a rare pathology. CASE REPORT: Patient: Male, 14 years old, cowboy, student, from Patos. Following a fall from a horse, the patient began to experience discomfort in the neck, occipital region, and shoulder, as well as a sensation of numbness and burning in the tongue, especially when moving his head laterally. The pain has an immediate onset, is unilateral, and is described as tingling or stabbing with moderate to severe intensity in the occipital region, neck, and shoulders, always following sudden lateral neck movement, along with changes in the tongue, such as numbness and a strange sensation. The pain lasts for an average of a few minutes, with complete improvement.Physical and neurological examinations are normal. X-ray and cervical MRI are normal.CONCLUSION: Neck-tongue syndrome, being a rare and still poorly recognized pathology, is difficult to diagnose. This results in significant delays in diagnosis and consequently poor management. Therefore, it is crucial to have more case reports for the recognition of this nosological entity.